Sistem Pendukung Keputusan Penentuan Jumlah dan Kualitas Sampah Daur Ulang Menggunakan Metode Weight Product - Sahyunan Harahap; Sumijan (Jurnal Informasi dan Teknologi, 2021)
The Sanitation Bureau of Panca Budi Univeristas of Development is a place for the utilization and processing of recycled waste, both organic and non-organic waste. In this case, processed recycled waste will get the best quantity and quality. Determination of the amount and quality of recycled waste using the Weihgt Product (WP) method in order to obtain a quality result of recycled waste that has the best quality as needed. Data collection was carried out by interviewing and conducting research in order to obtain data in the form of exel with a sample size of 22. The data that has been collected, processed and analyzed before being used as input and output as a basis for learning or training. Based on calculations using the product weight method, it can be used as a reference in making a decision support system by weighting, multiplying and dividing each alternative. The value of A11 shows the largest value which is the best alternative choice and based on the test data is cardboard waste. So this research is very appropriate in making the right decision to determine the type of quality waste for recycling.